(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2017)
The study investigated the relationship between being proactive and customer retention in upscale restaurants in the hospitality industry in Port Harcourt, Rivers State, Nigeria. The specific objectives were to determine the relationship between being proactive and low customer defection, repeat purchase and high referrals. The study adopted quasi-experimental design which employed survey approach gathered data from 144 senior employees who work in 24 upscale restaurants in Port Harcourt. A well-structured questionnaire containing 26 items, with nine demographic items was used to elicit primary data from the respondents. After data editing, and reliability analysis of the instrument, inferential statistics was conducted with the help of Statistical Package For Social Sciences (SPSS). The result of the inferential statistical analysis revealed that being proactive positive and significant relationship with low customer defection, repeat purchase and high referrals respectively. The study concluded that being proactive by organizational managers is an important marketing strategy capable of enhancing customer retention. It was therefore recommended that management should ensure that their customer retention programmes are proactive rather than reactive.